ANALISA KINERJA OIL COOLER DENGAN PENDEKATAN FINITE ELEMENT ANALYSIS (FEA) PADA BEBAN DAYA YANG DIGUNAKAN GENERATOR DI KM TRANS MITRAMAS 5 - Teguh Binardi; Kamal, Mustopa; Ade Hermawan; Achmad Syarifudin; Doly Andrian Harahap; Marsono, Marsono; Aprizha Muhammad Fadhil (Bajang Institute, 2025)
This study analyzes the thermal performance of a shell and tube type oil cooler installed in the generator of the KM Trans Mitramas 5 fishing vessel, located in Samudera Bitung Fishing Port, North Sulawesi. Using the Finite Element Analysis (FEA) method and ANSYS simulation, the study investigates how thermal loads, derived from different power levels (70 kW, 130 kW, and 200 kW), affect heat transfer effectiveness and temperature distribution. The results show increasing Log Mean Temperature Difference (LMTD) and hotspot patterns correlating with higher thermal loads. Simulation findings confirm the oil cooler’s capability to stabilize oil temperature under varying loads, with LMTD values of 38.12°C, 53.00°C, and 56.18°C respectively. The system remains efficient, though routine maintenance and proper material selection are recommended for long-term performance